Human resources management strategies in enhancing transportation performance and safety in Indonesia - Sihombing, Sarinah; Simarmata, Juliater; Banjarnahor, Astri Rumondang; Farisyi, Sofwan; Suvittawat , Adisak (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to investigate the strategic role of Human Resource Management (HRM) practices—particularly training and development, performance management, and organizational innovation in improving transportation performance and safety in Indonesia. It also explores the moderating effect of employee welfare on these relationships, responding to the growing demands of digital transformation and safety standards in the transportation sector. Methodology: A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 360 respondents working in the land transportation sector across Indonesia through structured questionnaires. Results: The findings confirm that training and development, as well as performance management, significantly influence both organizational innovation and transportation safety. Organizational innovation also positively affects transportation performance, which in turn enhances safety. However, the moderating effect of employee welfare on the innovation–performance relationship was found to be statistically insignifican. Conclusions: High-quality HRM practices, especially in training and performance management, are crucial for enhancing both operational performance and safety in Indonesia’s transportation sector. While innovation contributes to performance, its full benefits may not materialize without stronger welfare systems. Companies should integrate safety-focused training, real-time performance tracking, and inclusive innovation mechanisms into their HR strategy to build a more resilient transportation workforce. Limitations: This study finds that employee welfare has not yet played a significant moderating role in boosting transportation performance through innovation. Most welfare initiatives remain basic, lacking integration with strategic innovation agendas. This limitation highlights a disconnect between employee well-being and organizational goals, which may affect long-term innovation sustainability. Contribution: The study contributes to HRM theory by validating the impact of training and performance management on transportation innovation and safety within a developing-country context. Practically, it provides a framework for transportation firms to align HR strategies with digitalization and operational safety goals. It also underscores the need for welfare policies that go beyond minimum standards to actively support innovation and performance excellence.